Versatile biocatalyst: lipase from Streptomyces gobitricini for ester synthesis and detergent innovation - Alzahrani, Areej Ali; Krayem, Najeh; Alonazi, Mona; Al-Ghamdi, Jihan M.; Horchani, Habib; Ben Bacha, Abir (Frontiers in Bioengineering and Biotechnology, 2025)
Background/objectivesThe growing demand for reliable and stable biocatalysts has spurred research into microbial lipases for diverse industrial applications. This study focused on enhancing the production and purification of a lipase from Streptomyces gobitricini (LipS.g).MethodsMaximal lipase activity (420 U/mL) was achieved during the stationary phase after 84 h of incubation at 45°C and pH 8.0, using 2% glucose and 2% yeast extract as carbon and nitrogen sources, respectively.ResultsCalcium, olive oil, and Tween, at 1%, significantly enhanced LipS.g production, highlighting the role of triglycerides and detergents in enzyme induction and substrate emulsification. The purified 50-kDa enzyme displayed maximal activity at 50°C and pH 9.0, with thermal stability between 40°C and 55°C and pH 5.0–10.0. While LipS.g efficiently hydrolyzed short and medium-chain triglycerides, it exhibited a preference for long-chain substrates, with a maximum reaction rate of 2500 μmol/min/mg and a Km value of 6.45 mM toward triolein (C18). LipS.g also demonstrated remarkable stability in detergent formulations, retaining more than 85% activity in the presence of surfactants, oxidizing agents, boron compounds, and enzyme inhibitors. Additionally, LipS.g catalyzed the esterification of oleic acid with starch and ethanol to produce starch oleate and ricinoleic acid.ConclusionThese findings establish LipS.g as a promising biocatalyst for applications in biocatalysis and detergent formulations, with potential uses in the food, beverage, cosmetic, and pharmaceutical industries.